Reduction of Source Current and Source Voltage Harmonics Using SHAPF - Sukumar, Preetha; Ramachandran, M.; Umamaheswari, K.; Maryia Chithra Mary, A. (Asian Journal of Electrical Sciences, 2018)
This paper investigate the source current and voltage harmonics reduction under unbalanced supply condition. The current harmonics produced are reduced by the Shunt active filter. In order to reduce the voltage harmonics Shunt active filter is not capable. So SHAPF is designed to compensate the source current and voltage harmonics. SHAPF is also used for compensation of reactive power and improve power quality. It also eliminates series and parallel resonance. The control technique for the SHAPF is based on the Instantaneous Reactive Power Theory. Both the real and reactive power are changed in terms of voltage component. In order to compensate the source current and load voltage harmonics the reference voltage is calculated. Simulations are carried out on MATLAB-Simulink and results are presented.